Vertical Integration and Exclusivity in Platform and Two-Sided Markets. - Lee, Robin S (American Economic Review, 2013)
This paper measures the impact of vertically integrated and exclusive software on industry structure and welfare in the sixth-generation of the US video game industry (2000-2005). I specify and estimate a dynamic model of both consumer demand for hardware and software products, and software demand for hardware platforms. I use estimates to simulate market outcomes had platforms been unable to own or contract exclusively with software. Driven by increased software compatibility, hardware and software sales would have increased by 7 percent and 58 percent and consumer welfare by $1.5 billion. Gains would be realized only by the incumbent, suggesting exclusivity favored the entrant platforms. (JEL D12, L13, L22, L63, L86)